EKSISTENSI ALAT BUKTI DALAM PENGADILAN (STUDI KOMPARATIF MENURUT HUKUM ISLAM DAN HUKUM POSITIF DI INDONESIA) - Azwar, Syahrul (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2018)
The formulation of this research  is: First, How is the existence  of evidence  in the judiciary according  to Islamic law? Second  What  is the existence  of evidence  in court  according  to positive  law in Indonesia? Third,  how  do  you compare the existence  of evidence  according  to Islamic law and  criminal procedural law? This type of research  is library research  (library research). Data collection uses reading techniques, citing information. This study concludes  that: First, according  to Islamic law, evidence  is anything  that has something  to do with an act, the evidence  can be used as evidence  to raise the confidence of the judge over the truth of a criminal act committed  by the defendant. Second, the evidence  according  to positive law is witness testimony,  expert  testimony,  letters, instructions  and  information from the defendant. Whereas  the positive law stipulates  that only legal evidence  instruments can be used  for verification.  Third, the position  of evidence  in Islamic law and  Positive Law is a tool to assist the process  of verification in criminal proceedings and  help the judge to obtain  confidence in an alleged act. Islamic law and positive law have several similarities, namely  the law governing  actions that are related to the soul or members of the body,  such as killing, injuring and so on